If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3a + 2 + 1 = 0 Reorder the terms: 2 + 1 + 3a = 0 Combine like terms: 2 + 1 = 3 3 + 3a = 0 Solving 3 + 3a = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 3a = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 3a = 0 + -3 3a = 0 + -3 Combine like terms: 0 + -3 = -3 3a = -3 Divide each side by '3'. a = -1 Simplifying a = -1
| 2(x+7)=(2x+14) | | (4x-11)=(x+6) | | 3x-5x+17=12-(6x+3) | | x(x+1)-3(x+1)= | | 8x^2-4x+2=0 | | 9+2m=-3-4m | | x(x+3)-5(x+3)= | | 45=0.5(6+3) | | -9x=-27 | | 6(k-5)-(2k-4)=7k | | 9(y-7)=8+8y | | 6y+1-2y=8+3y+6 | | -9(n-6)=-8n-9 | | 4y+3y=6y+3 | | -3(4x-6)+8=-12x+26 | | 0.12(y-7)+0.04y=0.20y-0.9 | | 10x^3-8x^2+2x=0 | | 34X-25=18 | | -9(x-8)+2=74 | | 2(4x+7)-5=8x+9 | | -x+3=22 | | 15t^4-2t^2+78=0 | | n/2-9=-5 | | 30=48t-16t^2 | | 3(2x+35)+5(x+1)=u | | (15+9)x(22-5)= | | u/12-8=-8 | | 44=2(3.14) | | -8(t-4)-(t+1)=4 | | 6x-4=24x+2 | | 5(x+2)+7=17 | | r/2+6=5 |